THE FORMATION OF THE MODERN SOCIO-ECONOMIC RELATIONS AS THE BASIS OF THE MARKET ECONOMY OF UKRAINE - Kovalchuk, T. O. (Science and Transport Progress, 2006)
The article examines the features of formation of new quality of socio-economic relations in Ukraine at the present stage.